A novel monoclonal antibody KMP1 has potential antitumor activity of bladder cancer by blocking CD44 in vivo and in vitro. (25th March 2018) - Chen, Yujin; Wang, Haifeng; Zuo, Yigang; Li, Ning; Ding, Mingxia; Li, Chong
Abstract: Bladder cancer becomes a serious medical and social concern due to its high recurrence and mortality rates. Thus, it is urgent to search a novel prognostic biomarker and targeted therapy with high sensitivity and specificity. In this study, we used the human bladder cancer cell line EJ as an immunogen to generate a novel mouse monoclonal antibody KMP1 that specifically bound to bladder cancer, and then, the antitumor effect of KMP1 against bladder cancer was investigated both in vivo and in vitro. The results showed that expression of the KMP1 epitope is consistent with clinical severity and prognosis of bladder cancer. Furthermore, KMP1 not only significantly inhibited the proliferation, migration, and adhesion of EJ cells in vivo, but also suppressed the xenograft tumor growth in nude mice compared with the control group treated with mIgG. Subsequently, the underlying mechanism of KMP1 against bladder cancer was explored via antigen affinity chromatography and mass spectrometry. CD44 located on the cytomembrane was found as the antigen of KMP1. Using RNA interference technology to knock down CD44 expression, we further identified that KMP1 has the antitumor activity by binding to CD44 and blocking its functions. In conclusion, KMP1 might be valuable for development as a promising specific diagnostic biomarker or targeted agent for bladder cancer. Abstract : KMP1 antigen is a novel mouse monoclonal CD44 antibody against bladder cancer. It was consistent with clinical severity and prognosis. KMP1 has an antitumor activity of bladder cancer by blocking CD44 in vivo and in vitro. KMP1 exerted potent therapeutic efficacy for bladder cancer.